Legal Protection of Women as Victim of Domestic Violence - Wantu, Fence M; Sarson, Mohamad Taufiq Zulfikar (Indonesian Journal of Advocacy and Legal Services, 2020)
This study aims to determine the extent of legal protection by the Women and Children Service Unit (PPA) of the Gorontalo City Resort Police Criminal Investigation Unit against women as victims of domestic violence and to find out what factors are obstacles to the efforts of the PPA Unit of the Criminal Investigation Unit Gorontalo Resort Police in tackling violence against women victims of Domestic Violence. Data collected through interviews and library research. Analysis of the data used is the data obtained will be analysed descriptively qualitatively describing the data obtained from field research (primary data), tested the truth then linked and analysed qualitatively with data obtained from library research (secondary). The results showed a form of legal protection by the PPA Unit of the Gorontalo Police Resort Criminal Investigation Unit against women as victims of domestic violence, namely preventive efforts by holding legal counselling in collaboration with the local government and further optimizing the performance of the Gorontalo City Resort Police Especially the PPA unit, repressive efforts that are in accordance with the rules of the Domestic Violence Protection Act. What factors hinder the efforts of the PPA Unit of the Gorontalo District Police Resort Criminal Investigation Unit in tackling violence against women victims of Domestic Violence, among others: Legal factors themselves, Law Enforcement Officers Factors, Factors or Facilities That Support Law Enforcement, Factors Society and Culture